Quality of life and physical activities of daily living among stroke survivors; cross‐sectional study - Sachini Ellepola; Nethuli Nadeesha; Ishara Jayawickrama; Anjali Wijesundara; Nimantha Karunathilaka; Priyamali Jayasekara (Wiley, 2022)
Abstract Aim To examine the relationship between quality of life (QoL), level of physical activities of daily living (PADL) and associated factors among stroke survivors during the acute stage as there is little evidence in Sri Lanka. Design We conducted a descriptive cross‐sectional study among conveniently recruited stroke survivors in Sri Lanka (n = 134). Methods QoL was assessed by the Short Form‐36 (SF‐36), while the PADL was assessed by the Barthel Index (BI). The relationship between SF36 and BI was assessed by Pearson correlation, while Multiple Linear Regression (MLR) was performed to determine the factors associated with QoL and PADL. Results The majority of the SF36 domains were below the average level of 50, while BI indicated that most of them belonged to either the severely or totally dependent category. Aphasia, disability, dysarthria, type of stroke, dyslipidaemia, smoking, alcohol consumption, geographical area and income were the associated factors of QoL, while disability of the face and limbs, dysarthria and smoking were the associated factors of PADL (p < .05).